SKEPTISISME DALAM HERMENEUTIKA FEMINIS FATIMA MERNISSI - Qaem Aulassyahied (UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
This paper explores the Fatima Mernissi of Hermeneutics with Feminism paradigm.Â According to him, one of the sources of discrimination against women is the interpretation the clericsÂ of the some hadith that are full of with a view of masculinity. Fatima Mernissi does not hesitate toÂ mention the narrators on Thabaqat companions, like Abu Hurariah which has narrated some hadithÂ recognition of the Prophet, however full of with interests that lead to hatred against women.Â Skepticism and excessive criticism, of Fatima Mernissi was found when there is no recognition thatÂ false hadiths, can occur because of a mistake narrators without the element of intent. The attitude ofÂ skepticism Fatima Mernissi also found when, citing the data source from the book of scholars byÂ adding a few words which caused it means to be biased, and also a negative view of the narrationsÂ that are considered misogynistic.Tulisan ini mengeksplorasi Hermeneutika Fatima Mernissi dengan paradigma Feminisme.Â Menurutnya, salah satu sumber diskriminasi terhadap perempuan adalah tafsiran para ulamaÂ terhadap beberapa hadis yang sarat dengan pandangan maskulinitas. Fatima Mernissi tidak seganÂ menyebutkan perawi pada Thabaqat sahabat, seperti Abu Hurariah yang telah meriwayatkanÂ beberapa hadis yang diakuinya dari Rasulullah namun sarat kepentingan dan tendensius yangÂ mengarah kepada â€œanti perempuanâ€. Sikap skeptis dan kritik berlebihan yang dilakukan oleh FatimaÂ Mernissi ditemukan ketika tidak ada pengakuan bahwa hadis palsu dapat terjadi karena kekeliruanÂ perawi tanpa adanya unsur kesengajaan. Sikap skeptisisme Fatima Mernissi juga ditemukan ketikaÂ mengutip sumber data dari kitab ulama dengan menyusupkan beberapa kata yang menyebabkanÂ maknanya menjadi bias dan memandang negatifriwayat-riwayat yang dianggap misoginis.